Microwave Materials Characterization - Costanzo, Sandra (IntechOpen, 2012)
Microwave Materials Characterization is an edited book discussing recent researches on basic and innovative measurement techniques for the characterization of materials at microwave frequencies, in terms of quantitative determination of their electromagnetic parameters, namely the complex permittivity and permeability. It is divided into two parts: Part 1, including original contributions on advanced techniques for the characterization of dielectric materials, and Part 2, devoted to the microwave characterization of biological tissues.